2022
DOI: 10.1039/d2ra00905f
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of chitosan nanoparticles encapsulating silymarin (Sil–CNPs) against SARS-CoV-2 (in silico and in vitro study)

Abstract: To develop a specific treatment against COVID-19, we investigated silymarin–chitosan nanoparticles (Sil–CNPs) as an antiviral agent against SARS-CoV-2 using in silico and in vitro approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
(73 reference statements)
0
20
0
Order By: Relevance
“… molecular docking experiments Srivastava, Tripathi, Unni, Hussain, Haque, Dasgupta, Singh, Mishra [24] Phytochemicals from the medicinal plants Molecular Docking Studies -Silybin, with their possible potential effectiveness in the treatment of COVID-19, reflect future possibilities in viral protease inhibition by the use of flavonoids -Silybin B demonstrated better binding and ADME properties compared with the currently endeavored drugs like Hydroxychloroquine and Lopinavir. molecular docking approach Kumar, Kashyap, Chowdhury, Kumar, Panwar, Kumar [25] Phytochemicals from the medicinal plants Docking analysis The present study demonstrated the binding potential of silymarin with Nsp15 and is capable of inhibiting viral replication, In vitro Loutfy, Abdel-Salam, Moatasim, Gomaa, Fattah, Emam, Ali, ElShehaby, Ragab, El-Din [26] Vero and Vero E6 cell lines 6.25, 12.5, 25, 50, 100, and 200 μg/m Silymarin against SARS-CoV-2 was through interference with viral attachment by blocking ACE2 receptor. Clinical trials Aryan, Farahani, Chamanara, Elyasi, Jaafari, Haddad, Sani, Ardalan, Mosaed [27] silymarin 70 mg The present study demonstrated there were not significant differences between the two groups in terms of symptoms resolution time, laboratory parameters (Serum creatinine level, C-reactive protein, Lymphocyte count, Atrial O 2 saturation, Length of need for supplement of O 2 AST), and hospitalization duration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… molecular docking experiments Srivastava, Tripathi, Unni, Hussain, Haque, Dasgupta, Singh, Mishra [24] Phytochemicals from the medicinal plants Molecular Docking Studies -Silybin, with their possible potential effectiveness in the treatment of COVID-19, reflect future possibilities in viral protease inhibition by the use of flavonoids -Silybin B demonstrated better binding and ADME properties compared with the currently endeavored drugs like Hydroxychloroquine and Lopinavir. molecular docking approach Kumar, Kashyap, Chowdhury, Kumar, Panwar, Kumar [25] Phytochemicals from the medicinal plants Docking analysis The present study demonstrated the binding potential of silymarin with Nsp15 and is capable of inhibiting viral replication, In vitro Loutfy, Abdel-Salam, Moatasim, Gomaa, Fattah, Emam, Ali, ElShehaby, Ragab, El-Din [26] Vero and Vero E6 cell lines 6.25, 12.5, 25, 50, 100, and 200 μg/m Silymarin against SARS-CoV-2 was through interference with viral attachment by blocking ACE2 receptor. Clinical trials Aryan, Farahani, Chamanara, Elyasi, Jaafari, Haddad, Sani, Ardalan, Mosaed [27] silymarin 70 mg The present study demonstrated there were not significant differences between the two groups in terms of symptoms resolution time, laboratory parameters (Serum creatinine level, C-reactive protein, Lymphocyte count, Atrial O 2 saturation, Length of need for supplement of O 2 AST), and hospitalization duration.…”
Section: Resultsmentioning
confidence: 99%
“…Silymarin was reported to inhibit the hepatitis C virus in vivo and in vitro by inhibiting hepatitis C virus entry, viral protein expression, RNA synthesis, and virus replication. It also inhibits the virus's cell-to-cell spread [24] , [25] . Silibinin, a combination of two stereoisomers, silibinin B and silibinin A, in equimolar ratio, is the main component of this complex extract and is the most active constituent of silymarin [26] , [27] .…”
Section: Introductionmentioning
confidence: 99%
“…Using crystal violet, the IC50 was determined at doses of 0.91, 12.2, and 0.80 mg/mL for CNPs, Sil, and Sil–CNPs, respectively, in virucidal/replication studies. These findings reveal the antiviral activity of Sil–CNPs against SARS [ 162 ].…”
Section: Anti-covid-19 Applications Of Chitosan Composites and Deriva...mentioning
confidence: 96%
“…Bioavailability’s and physicochemical properties’ improvement of silymarin. To develop a specific treatment against COVID-19, Loutfy et al [ 257 ] investigated silymarin–CS NPs (Sil–CNPs) as an antiviral agent against SARS-CoV-2 using in silico and in vitro approaches. Docking of Sil (silymarin) and CNPs was carried out against SARS-CoV-2 spike protein using AutoDock Vina.…”
Section: Cs-based Dosage Forms and Drug Delivery Systems For Antiviralsmentioning
confidence: 99%